Development of a Lampung Language Vocabulary Learning Module to Improve Elementary School Student Learning Outcomes - Syukri, Ridwan; Ariyani, Farida; Rusminto, Nurlaksana Eko (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
The Lampung language vocabulary learning module is designed to improve the learning outcomes of fifth grade students at Sekolah Dasar (SD) Negeri Gilih Karang Jati. However, in reality, student learning outcomes are still not good, especially in learning Lampung language vocabulary. The aim of this research is to determine student learning outcomes in Lampung language vocabulary subjects. The data obtained in this research was analyzed using experimental methodology with a one group pretest posttest research design. This type of research is referred to as research and development (R&D) and is associated with ADDIE theory. The Lampung language vocabulary learning module has been verified by material, media and language experts and its usefulness has also been assessed based on teacher and student responses. Media experts obtained a valid percentage score of 0.93%, language experts obtained a valid percentage score of 0.88%, and material experts obtained a valid percentage score of 0.91%. The average percentage of educators' practicality test scores was 97.12% and students' practicality scores were 98.39%. The results of this research were analyzed using t test calculations, data analysis showed that there was a significant difference between before and after treatment using the Lampung language vocabulary learning module, with the achieved value of 0.000 < 005. Based on the research results, the implementation of the Lampung language vocabulary-based learning module can be achieved in helping fifth grade students at SD Negeri Gilih Karang Jati achieve better learning outcomes.